Perancangan Strategi Kreatif Konten Visual Sosial Media Situ Cileunca Pangalengan Kab. Bandung - Muthmainnah, Ligar; Yusup, Nuke Rahmadina (Visualita Jurnal Online Desain Komunikasi Visual, 2023)
The city of Bandung has natural beauty that is still beautiful, especially in the Bandung Regency area. There are still many green lands that have now begun to be managed properly, neatly arranged, and made more comfortable for visitors. One of them is Situ Cilenca located in Pangalengan, Bandung Regency, is a tourist destination that has views of green hills and dense forests and vast expanses of lakes. In addition to having amazing natural beauty, Situ Cileunca offers several game attraction facilities offered in the form of outbound training such as rafting, flying fox, ATVs and also have a camping ground. With an affordable entrance ticket price, Situ Cileunca already has facilities that can be said to be complete. Moreover, currently the Bandung Regency Disbudpar is arranging the existing facilities in Situ Cileunca in stages. But unfortunately Situ Cileunca has not made maximum use of social media, so it is not uncommon for many who do not know Situ Cileunca in detail. This design was made to implement creative strategies in social media to maximize the promotion of low budget high impact for Situ Cileunca. In collecting data, this design uses a mix method, by conducting interviews, observations, and distributing questionnaires to Bandung residents aged 19-25 years. The results of this plan can be seen that by maximizing social media will be more effective in introducing and disseminating information about Situ Cileunca Pangalengan Kab. Bandung.